Training on waste management into a useful product in Bunipah Village, Banjar Regency - Nisa, Mufatihatul Aziza; Wati, Nur Lina; Nur, Aprilia Artati; Fitria, Fitria; Apriani, Karina Nurfatma; Fajrin, Reki Ranggafu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Garbage is anything that is no longer used, disliked, even something that must be thrown away. Lack of public awareness and knowledge regarding waste disposal and waste management will result in community participation itself in protecting the surrounding environment. This community service program was carried out at RT 03 Bunipah Village, Aluh-Aluh District, Banjar Regency, South Kalimantan. This program is conducted online through WhatsApp groups. The goal is to increase public knowledge and insight about waste and its management in order to form awareness and good behavior for waste management. The community is expected to be able to manage waste into useful products such as compost and crafts. The results of the Wilcoxon test on the results of the pre-post test of knowledge about waste management showed differences in the knowledge and attitudes of the community before and after the intervention was given in the form of waste management training through posters, booklets, and videos, while the results of the t-test on the results of the pre-post test of attitudes about waste management The results showed that there was no difference in the knowledge and attitudes of the community before and after being given the training.